Impact of precompetitive training on metabolites in modern pentathletes - Loureiro, L. L.; Ferreira, T. J.; da Costa, C. S. C.; Fidalgo, T. K. S.; Valente, A. P.; Pierucci, A. P. T. R. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Modern pentathlon is a multidisciplinary sport that involves exhaustive training which can cause tissue damage and metabolic changes. However, few studies have evaluated the metabolic changes that occur in pentathletes. Accordingly, we aimed to evaluate the metabolomic profile of pentathletes during a 3-week training period before competition using nuclear magnetic resonance.